Coal Fly Ash Beneficiation Treatment of Acid Mine Drainage with Coal Fly Ash - Akinyemi, Segun A.; Gitari, Mugera W. (IntechOpen, 2018)
The present book deals with various, very significant topics of coal fly ash beneficiation, such as treatment of acid mine drainage with coal fly ash, toxic metal adsorption using coal fly ash, recovery of metals from coal fly ash and phytoreclamation of abandoned acid mine drainage site after treatment with coal fly ash, the status of research in coal fly ash utilization and applications and some other related topics in this growing and increasingly important research area. Overall, coal fly ash beneficiation has come to assume an important role in most areas of waste management research today. Continued growth and emphasis on scientific research is expected in all areas of waste management and conversion of waste to wealth technologies.